Hard X-ray generation from ZnO nanowire targets in a non-relativistic regime of laser-solid interactions - Samsonova, Zhanna; Hoefer, Sebastian; Hollinger, Richard; Kaempfer, Tino; Uschmann, Ingo; Roeder, Robert; Trefflich, Lukas; Rosmej, Olga; Foerster, Eckhart; Ronning, Carsten; Kartashov, Daniil; Spielmann, Christian (Applied Sciences, 2018)
We present a detailed investigation of X-ray emission from both flat and nanowire zinc oxide targets irradiated by 60 fs 5 × 1016 W/cm2 intensity laser pulses at a 0.8 μm wavelength. It is shown that the fluence of the emitted hard X-ray radiation in the spectral range 150-800 keV is enhanced by at least one order of magnitude for nanowire targets compared to the emission from a flat surface, whereas the characteristic Kα line emission (8.64 keV) is insensitive to the target morphology. Furthermore, we provide evidence for a dramatic increase of the fast electron flux from the front side of the nanostructured targets. We suggest that targets with nanowire morphology may advance development of compact ultrafast X-ray sources with an enhanced flux of hard X-ray emission that could find wide applications in highenergy density (HED) physics.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Laser plasma emission; Laser-matter interaction; Nanostructured arrays; Ultrashort laser pulses; X-ray generation; X-ray spectroscopy